Die fragmentierte Stadt Exklusion und Teilhabe im öffentlichen Raum - Krusche, Jürgen (De Gruyter, 2022)
Wherever people live closely together, there is competition and displacement. We practically take it for granted thatmany public places cannot be used equally by different groups of people. This assumption goes almost unnoticed,and is counter to the ideals of a democratic, open society with equalrights for all its members. How do people who exist at the marginsof society (or see themselves as existing there) experience publicurban spaces? Where do they feel welcome, and where do they feelunwanted? Where, how, and why do use conflicts arise? The projectDie fragmentierte Stadt-the fragmented city-pursues answers tothese questions.A collection of observations, walks, and encounters that took placeover the course of three years in Berlin, Graz, and Zurich form thefoundation of four artistic ethnographic approaches to experiencesof exclusion and appropriation strategies. Photographic, audio-visual,performance, and verbal investigations led to the development ofthe ideas, insights, and products introduced by the texts, images, and videos in this volume.